Control of Simian Immunodeficiency Virus SIVmac239 Is Not Predicted by Inheritance of Mamu-B*17-Containing Haplotypes - Wojcechowskyj, Jason A. (American Society for Microbiology, 2007)
It is well established that host genetics, especially major histocompatibility complex (MHC) genes, are important determinants of human immunodeficiency virus disease progression. Studies with simian immunodeficiency virus (SIV)-infected Indian rhesus macaques have associated Mamu-B*17 with control of virus replication. Using microsatellite haplotyping of the 5-Mb MHC region, we compared disease progression among SIVmac239-infected Indian rhesus macaques that possess Mamu-B*17-containing MHC haplotypes that are identical by descent. We discovered that SIV-infected animals possessing identical Mamu-B*17-containing haplotypes had widely divergent disease courses. Our results demonstrate that the inheritance of a particular Mamu-B*17-containing haplotype is not sufficient to predict SIV disease outcome.